Mesenchymal Stem Cells Combined with Tissue Fusion Technology Promoted Wound Healing in Porcine Bowel Anastomosis - Hong Pan; Ping Keun Lam; See W. Tong; Kevin K. Leung; Anthony Y. Teoh; Enders K. Ng (Hindawi Limited, 2020)
Objective. To evaluate the possible biological effect of allogenic mesenchymal stem cells (MSCs) combined with tissue fusion technology on the anastomosis. Methods. Sixteen pigs were divided into a 7 d group and 14 d group, each of which was further subdivided into an MSC-treated group and a control group. Five anastomoses per animal were established using LigaSure ForceTriad (Covidien, MA, USA), a tissue sealing system. Cell migration and tissue-specific differentiation potency, in addition to potential cytokine and genetic changes, were investigated. Results. There were no significant between-group differences in postoperative complications and anastomosis burst pressure. The number of proliferating cell nuclear antigen- (PCNA-) positive cells was significantly higher in the MSC-treated group as compared with that in the control group (P=0.021). Labeled MSCs were found in the mucosal layer, villus, and lamina propria, as well as in the lamina muscularis mucosae, where they exhibited characteristics of smooth muscle cells. Conclusions. Grafted MSCs significantly promoted epithelial and connective cell proliferation and maintained their cell migration capacity and differentiation potential in the fused anastomotic tissues, without causing severe postoperative complications.